The Effect of the Use of Kosica Media (Light Properties Box) on the Understanding of the Concept of Light Properties in Grade 4 Elementary School Students - Cahya Amalia Ramadhanti; Wati Sukmawati (Jurnal Penelitian Pendidikan IPA, 2025)
This study aimed to examine the effect of KOSICA (Box of Light Properties) media on elementary students’ conceptual understanding of light properties. The research was conducted at SDN Duren Tiga 13 Pagi, South Jakarta, using a quasi-experimental design involving two groups: control and experimental. The experimental group learned using KOSICA, while the control group received conventional instruction. An independent samples t-test revealed a significant difference between the groups (t = -4.460, p = 0.000), with higher post-test scores in the experimental group. Additionally, Rasch model stacking analysis showed that most students in the experimental class improved after the intervention. These findings suggest that KOSICA is an effective contextual tool to enhance science learning in elementary schools.